Development an Achievement Test on the Subject of “Basic Compounds in the Structure of Living Things” - Yalinkilic, Funda; Gul, Seyda (Science Insights Education Frontiers, 2023)
The aim of this study is to develop a valid and reliable achievement test on the subject of ‘Basic Compounds in the Structure of Living Things’. During the preparation of the draft form of the test, a 32 item-question pool was created by the researchers in the light of the relevant literature. Then, these questions were presented to expert opinion in terms of language, intelligibility and content. This draft test with 32 multiple choice questions, was applied to 252 students studying at three different high schools. Item difficulty and item discrimination indices were calculated for the data obtained. After the item analysis, seven questions were removed from the test. Thus, the average item difficulty of the 25-question achievement test was calculated as 0.44, and the average item discrimination was 0.44. The KR-20 reliability coefficient of the test was calculated as 0.75. This result shows that the test is of medium difficulty and excellent discriminative reliability. In addition, according to the revised Bloom taxonomy, seven of the questions in the test are at the level of remembering, fifteen at the level of understanding, two at the level of application and one at the level of evaluation.